Critical theory : the key concepts - Felluga, Dino Franco (Routledge key guides, 2015)
"Critical Theory: The Key Concepts introduces over 200 widely-used terms, categories and ideas drawing from new historicism, postmodernism, psychoanalysis, Marxism, narratology and other approaches. Entries range from concise definitions to longer explanatory essays and include terms such as :EgoDesireConsumptionHypertextKitschMisogynyQueer StudiesSymbolSuperstructureRaceFeaturing cross-referencing throughout, a substantial bibliography and index, this accessible and easy-to-use guide is an invaluable introduction for anyone studying critical theory. "--